A study on fluoride detection and assembly of hydroxyaromatic aldoximes caused by tetrabutylammonium fluoride1. Issue 11 (21st March 2015) - Tarai, Arup; Baruah, Jubaraj B.
<x xml:space="preserve">Abstract</x> Different assemblies formed by the interactions of tetrabutylammonium fluoride with hydroxy-aromatic oximes show characteristic optical properties.